PELATIHAN PEMBELAJARAN BERBASIS ICT KEPADA GURU BAHASA INGGRIS - Yanuarti Apsari; Ida Lisdawati; Euis Rina Mulyani (Abdimas Siliwangi, 2020)
ICT-based learning is very potential to make the learning process more effective. This training activity was followed by English teachers. The purpose of this activity is to improve teachers’ skills in integrating ICT in the learning process. The steps of activities carried out in community service activities include several stages such as a) the analysis stage, b) the design stage, c) the content development staged) the training stage and e) the evaluation stage. In the analysis stage, the team analyzed difficulties faced by the teacher in English subjects. Then, the results of this analysis stage were used as a reference at the design stage. At the Design stage, the team determined topics used in the training and designed content related to the use of  ICT-based Learning model. Then, in the content development stage, the team developed content in the form of Google classroom development integrated with  Canva and Kahoot. Then, at the implementation stage, training on ICT-based learning models is carried out. The results of this training indicate an increase in teacher competence in the ability to use ICT as a learning medium. Thus, the learning process becomes more effective and becomes more interesting.